Введение в инженерную деятельность / ДО 2021 (12.03.01): электронный курс - Мойзес Б. Б. Борис Борисович; Гольдштейн А. Е. Александр Ефремович; Калиниченко А. Н. Алексей Николаевич; Фёдоров Е. М. Евгений Михайлович (Томск, TPU Moodle, 2021)
Заглавие с экрана